2011
DOI: 10.1017/s175173111100036x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ad libitum and restricted feeding on early production performance and body composition of Yorkshire pigs selected for reduced residual feed intake

Abstract: Residual feed intake (RFI), defined as the difference between observed and expected feed intake based on growth and backfat, has been used to investigate genetic variation in feed efficiency in cattle, poultry and pigs. However, little is known about the biological basis of differences in RFI in pigs. To this end, the objective of this study was to evaluate the fifth generation of a line of pigs selected for reduced RFI against a randomly selected Control line for performance, carcass and chemical carcass comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
7
20
0
Order By: Relevance
“…Effects of selection for RFI on utilization of ME The higher energy expenditure in RFI+ piglets (Table 2) indicated that the efficiency of ME utilization was higher for RFI− than for RFI+ piglets when fed restrictively, and this agrees with results of other studies comparing a low RFI line to a control line (Boddicker et al, 2011a and2011b). Additionally, our study indicated that genetic selection, based on performance during the fattening period (from 35 kg onward; Gilbert et al, 2007) also affected metabolism during earlier stages of growth.…”
supporting
confidence: 88%
“…Effects of selection for RFI on utilization of ME The higher energy expenditure in RFI+ piglets (Table 2) indicated that the efficiency of ME utilization was higher for RFI− than for RFI+ piglets when fed restrictively, and this agrees with results of other studies comparing a low RFI line to a control line (Boddicker et al, 2011a and2011b). Additionally, our study indicated that genetic selection, based on performance during the fattening period (from 35 kg onward; Gilbert et al, 2007) also affected metabolism during earlier stages of growth.…”
supporting
confidence: 88%
“…The extent of intestinal nutrient uptake greatly relies on the interplay between digestive secretions, the intestinal absorptive surface and the permeability of the intestinal epithelium [6,7]. More feed efficient animals consume less feed based on their growth and maintenance requirements [8]. Since the FI substantially influences the size and energy requirement of the intestine to degrade the ingested feed [911], more feed efficient animals should have a smaller GIT and hence lower energy demands for basal maintenance of the GIT [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving feed effi ciency of livestock is an important goal for sustainability and profi tability. Residual feed intake (RFI) is a measure of production effi ciency that is calculated by determining the difference between the observed feed intake and expected feed intake of an individual animal based on performance (Koch et al, 1963;Boddicker et al, 2011). Animals with a low RFI are more feed effi cient than animals with a high RFI and maintain similar growth performance.…”
Section: Introductionmentioning
confidence: 99%